Ответы и объяснения

  • Yena
  • главный мозг
2014-02-09T19:08:25+04:00
 \sqrt{32}cos^{2}\frac{13\pi}{8}-\sqrt{32}sin^{2}\frac{13\pi}{8}=\sqrt{32}(cos^{2}\frac{13\pi}{8}-sin^{2}\frac{13\pi}{8})= \\ =\sqrt{16*2}*cos(2*\frac{13\pi}{8})=4\sqrt{2}*cos\frac{13\pi}{4}=4\sqrt{2}*cos(\frac{8\pi}{4}+\frac{5\pi}{4})= \\ =4\sqrt{2}*cos(2\pi+\frac{5\pi}{4})=4\sqrt{2}*cos\frac{5\pi}{4}=4\sqrt{2}*cos(\frac{4\pi}{4}+\frac{\pi}{4})= \\ =4\sqrt{2}*cos(\pi+\frac{\pi}{4})=-4\sqrt{2}*cos\frac{\pi}{4}=-4\sqrt{2}*\frac{\sqrt2}{2}=-4
а теперь можно это же только короче?
просто пропусти некоторые шаги, которые тебе понятны